DEVELOPMENT OF INDUSTRIAL ENTERPRISES AND ANALYSIS OF THE FACTORS OF THEIR COMPETITIVENESS (World Economics and Finance Bulletin, 2024)
Since the widespread use of factors of competitiveness of industries is an important factor, the article examines the issues of modern competition to identify potential buyers of an enterprise, study and satisfy their desires, and ensure the expansion of market activity. The paper presents practical proposals and recommendations based on the analysis to improve the competitiveness of industrial enterprises.